Untranslated Javanese Words in Translation of Okky Madasari’s Novel The Years of Voiceless - I Dewa Putu Wijana (Universitas Sanata Dharma, 2021)
This article will try to investigate the Javanese words which are left untranslated found in Okky Madasari’s novel that has been translated into English under the title “The Years of Voiceless”. The research is directed to reveal the reasons that motivate the translators not to translate those words. By applying sociolinguistic theory which strongly believes that linguistic performances are influenced by extralinguistic factors, it is found that Javanese words referring to specific cultural entities, such as address terms, religious beliefs, foods and drinks, performing and architectural arts, and politics are left untranslated.